A estrutura da auto-avaliação da saúde entre idosos: projeto Bambuí The structure of self-rated health among older adults: the Bambuí health and ageing study (BHAS) - Maria Fernanda Lima-Costa; Josélia O A Firmo; Elizabeth Uchôa (Universidade de São Paulo, 2004)
OBJETIVO: Determinar os fatores associados à auto-avaliação da saúde entre idosos, considerando-se cinco dimensões: sociodemográfica, suporte social, hábitos de vida relacionados à saúde, condições de saúde e acesso e uso de serviços de saúde. MÉTODOS: Dos 1.742 idosos (>60 anos) residentes na cidade de Bambuí (Minas Gerais), 1.516 (87,0%) participaram do estudo. As informações foram obtidas por meio de entrevistas, exames físicos e laboratoriais. RESULTADOS: A auto-avaliação da saúde como boa/muito boa, razoável e ruim/muito ruim foi relatada, respectivamente, por 24,7%, 49,2% e 26,1% dos participantes. As seguintes características apresentaram associações independentes e positivas com pior percepção da saúde: suporte social (insatisfação com os relacionamentos pessoais e menor freqüência a clubes ou associações), condições de saúde (sintomas depressivos/ansiosos nas últimas duas semanas, queixa de insônia nos últimos 30 dias, maior número de medicamentos prescritos usados nos últimos 30 dias) e acesso/uso de serviços de saúde (queixas quando necessita de serviços médicos, maior número de consultas médicas nos últimos 12 meses e maior número de internações hospitalares no período). Associação negativa e independente foi encontrada para renda domiciliar mensal (<2,0 vs >4 salários-mínimos). CONCLUSÕES: Os resultados mostraram uma estrutura multidimensional da auto-avaliação da saúde em idosos, compreendendo a situação socioeconômica, suporte social, condições de saúde (destacando-se a saúde mental) e acesso e uso de serviços de saúde. OBJECTIVE: To determine factors associated with self-rated health among older adults, considering five dimensions: sociodemographic variables, social support, lifestyle risk factors, health status, and access to/use of healthcare services. METHODS: Of the 1,742 older adults (>60 years) living in the town of Bambuí (southeastern Brazil), 1,516 (87.0%) participated in the study. Information was obtained by means of standardized interviews and physical and laboratory exams. RESULTS: Self-rated health as good/very good, reasonable, and poor/very poor was reported by 24.7%, 49.2%, and 26.1% of subjects, respectively. The following characteristics showed independent positive associations with worse self-rated health: social ties (dissatisfaction with social network, attendance to clubs and associations), health status (symptoms of depression/anxiety in the last two weeks, sleeplessness in the last 30 days, greater number of prescribed medications used in the last 30 days), and access to/use of healthcare services (complaints when seeking medical care, greater number of medical appointments in the last 12 months, greater number of hospital admissions in the last 12 months). An independent negative association was found with monthly family income (<2.0 vs. >4 minimum wages). CONCLUSIONS: Our results show that self-rated health among older adults is multidimensional in structure, being influenced by socioeconomic conditions, social support, health status (with emphasis on mental health), and access to/use of healthcare services. This structure resembles the definition of health adopted by the World Health Organization (an individual's "physical, mental and social well-being").